Dr. Y. S. Kulkarni (1910-2008) Obituary - Deshpande, Mukund V. (Indian Journal of Microbiology, 2008)

Development of mycoinsecticide for the control of insect pests: comparative evaluation of metarhizium isolates to identify strains for commercialization - Deshpande, Mukund V.; Kulkarni, Shuklangi A.; Ghormade, Vandana; Kapoor, Manisha; Chavan, Santosh B.; Kulkarni, Grish; Shouche, Yogesh (New Biotechnology, 2009)

Dimorphism and hydrocarbon metabolism in Yarrowia lipolytica var. indica - Palande, A. S.; Kulkarni, S. V.; Leon-Ramirez, C.; Campos-Gongora, E.; Ruiz-Herrera, J.; Deshpande, Mukund V. (Archives of Microbiology, 2014)
Yarrowia lipolytica is able to metabolize high Mr hydrophobic natural compounds such as fatty acids and hydrocarbons. Characteristically, strains of Y. lipolytica can grow as populations with variable proportions of yeast and filamentous forms. In the present study, we describe the dimorphic characteristics of a variant designated as Y. lipolytica var. indica isolated from petroleum contaminated sea water and the effect of cell morphology on hydrocarbon metabolism. The variant behaved as a yeast monomorphic strain, under conditions at which terrestrial Y. lipolytica strain W29 and its derived strains, grow as almost uniform populations of mycelial cells. Using organic nitrogen sources and N-acetylglucosamine as carbon source, var. indica was able to form mycelial cells, the proportion of which increased when incubated under semi-anaerobic conditions. The cell surface characteristics of var. indica and W29 were found to be different with respect to contact angle and percent hydrophobicity. For instance, percent hydrophobicity of var. indica was 89.93 +/- A 1.95 while that of W29 was 70.78 +/- A 1.1. Furthermore, while all tested strains metabolize hydrocarbons, only var. indica was able to use it as a carbon source. Yeast cells of var. indica metabolized hexadecane with higher efficiency than the mycelial form, whereas the mycelial form of the terrestrial strain metabolized the hydrocarbon more efficiently, as occurred with the mycelial monomorphic mutant AC11, compared to the yeast monomorphic mutant AC1.
Keywords: Hexadecane metabolism; Yarrowia lipolytica; Yeast-mycelium transition

Development of metarhizium anisopliae as a mycoinsecticide: from isolation to field performance - Tupe, Santosh G.; Pathan, Ejaj K.; Deshpande, Mukund V. (Jove-Journal of Visualized Experiments, 2017)
A major concern when developing commercial mycoinsecticides is the kill speed compared to that of chemical insecticides. Therefore, isolation and screening for the selection of a fast-acting, highly virulent entomopathogenic fungus are important steps. Entomopathogenic fungi, such as Metarhizium, Beauveria, and Nomurea, which act by contact, are better suited than Bacillus thuringiensis or nucleopolyhedrosis virus (NPV), which must be ingested by the insect pest. In the present work, we isolated 68 Metarhizium strains from infected insects using a soil dilution and bait method. The isolates were identified by the amplification and sequencing of the ITS1-5.8S-ITS2 and 26S rDNA region. The most virulent strain of Metarhizium anisopliae was selected based on the median lethal concentration (LC50) and time (LT50) obtained in insect bioassays against III-instar larvae of Helicoverpa armigera. The mass production of spores by the selected strain was carried out with solid-state fermentation (SSF) using rice as a substrate for 14 days. Spores were extracted from the sporulated biomass using 0.1% tween-80, and different formulations of the spores were prepared. Field trials of the formulations for the control of an H. armigera infestation in pigeon peas were carried out by randomized block design. The infestation control levels obtained with oil and aqueous formulations (78.0% and 70.9%, respectively) were better than the 63.4% obtained with chemical pesticide.